1998
DOI: 10.1111/j.1365-2621.1998.tb15790.x
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Bonds Influence the Heat‐induced Gel Properties of Chicken Breast Muscle Myosin

Abstract: The functions of thiol groups in the denaturation, aggregation and gelation of chicken breast muscle myosin during heating in 0.6M NaCl, 50mM sodium phosphate buffer, pH 6.5, was investigated by inhibiting disulfide (SS) bond formation using dithiothreitol (DTT). The endotherm of myosin heated in the presence or absence of DTT had similar thermal transition temperatures. Preventing SS bond formation increased the onset temperature for aggregation and gelation and decreased the elastic-like properties of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…Similar trends were observed as a result of pH induced folding and unfolding of cod myosin [15]. In rabbit myosin it has been reported that only one fifth of its reactive sulphydryl groups is located in the myosin light chain while remaining in the head region [32]. The increased reactive sulphydryl groups indicated possible structural transitions in the head region of myosin [29].…”
Section: Reactive Sulphydryl Groupssupporting
confidence: 79%
“…Similar trends were observed as a result of pH induced folding and unfolding of cod myosin [15]. In rabbit myosin it has been reported that only one fifth of its reactive sulphydryl groups is located in the myosin light chain while remaining in the head region [32]. The increased reactive sulphydryl groups indicated possible structural transitions in the head region of myosin [29].…”
Section: Reactive Sulphydryl Groupssupporting
confidence: 79%
“…Previous literatures have showed the importance of chemical forces in heat-induced protein gels. Smyth et al (1998) found that hardness of myosin gel could be weakened by adding dithiothreitol (DTT) to prevent the formation of disulfide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literatures have showed the importance of chemical forces in heat-induced protein gels. Smyth et al (1998) found that hardness of myosin gel could be weakened by adding dithiothreitol (DTT) to prevent the formation of disulfide bonds. Liu and Hsieh (2007) studied the molecular interactions of protein gels by adding DTT, urea and other reagents, and they concluded that non-covalent bonds played a more important role than disulfide bonds in the formation of heat-induced protein gels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2B) indicates the involvement of intermolecular disulfide bonds in network formation at the higher cooking temperatures (Smyth, Smith, & O'Neill, 1998;Sugeta, Go, & Miyazawa, 1973). In summary, Raman spectroscopy revealed the structural changes in protein secondary structure and that this information is useful to predict the EPT even after storage time up to 8 days.…”
Section: Discussionmentioning
confidence: 95%